Improving the ID3 Algorithm By Filtering Out Attributes With Values Of 0 or 1 - Chuenprasertsuk, Pinyarat; Jearanaitanakij, Kietikul (My University, 2022)
The iterative Dichotomiser 3 (ID3) algorithm is a classification algorithm that generates a decision tree, and it is one of the most simple and well-known tools. However, there is still room for improvement. This paper aims to reduce the running time of generating a decision tree by ignoring attributes that have an information gain value of 0 or 1 and the experiment result shows that the improved ID3 algorithm can significantly reduce the running time by more than 10 percent when compared with the traditional ID3 algorithm.
Keywords: Classification algorithm; Decision tree; ID3 algorithm; Information gain